Characteristic of shoulder and hip rotation range of motion in adolescent tennis players - Chang, B. F.; Liu, C. C.; Chang, H. Y. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Adolescent tennis players require sufficient hip and shoulder flexibility to achieve the kinetic chain of a tennis stroke or serve. Hence, the objective of this study is to measure the glenohumeral joint internal and external rotation (IR and ER, respectively) and hip ER range of motion (ROM) and to compare these parameters between experienced and beginner-level adolescent tennis players.